The Relationship Between Intrapersonal Intelligence and Physical Education Learning Outcomes in Class VII Students of SMP Negeri 6 Huamual Belagang - Iswan, La Ode; Rumahlewang, E.; Matitaputy, J. (International Journal of Education, Information Technology, and Others, 2024)
This research aims to determine whether there is a relationship between Intrapersonal Intelligence and Physical Education Learning Outcomes in Class VII Students of SMP Negeri 6 Huamual Behind.. This research is quantitative research. The object of this research was 22 class VII students of SMP Negeri 6 Huamual Behind. The results of research regarding the relationship between intrapersonal intelligence and physical education learning outcomes in class VII students at SMP Negeri 6 Huamual Behind are in the high category, namely; The total score of the intrapersonal intelligence variable (X) = 1528 while the total score of the learning outcome variable (Y) = 1800, the r-count value = 0.710503 while the r-table = 0.4227. The conclusion of this research is that there is a relationship between intrapersonal intelligence and physical education learning outcomes in class VII junior high school students